2017
DOI: 10.3389/fmed.2017.00214
|View full text |Cite
|
Sign up to set email alerts
|

Association between Sleep Patterns and Health in Families with Exceptional Longevity

Abstract: BackgroundSleep patterns such as longer sleep duration or napping are associated with poor health outcomes. Although centenarians and their offspring demonstrate a delayed onset of age-related diseases, it is not known whether they have healthier sleep patterns or are protected against the negative effects of sleep disturbances.MethodsData on sleep patterns and health history were collected from Ashkenazi Jewish subjects of the Longevity Genes Project using standardized questionnaires. Participants included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…Although some studies indicated that centenarians represent a prototype of successful aging (12), poor sleep quality is relatively high in this population (13,14). In addition, both the symptoms and influencing factors of sleep problems in long-lived populations have varied patterns compared to the symptoms and factors among younger generations (15,16). Thus, it is imperative to verify tools for measuring sleep quality among this exceptionally aged population.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies indicated that centenarians represent a prototype of successful aging (12), poor sleep quality is relatively high in this population (13,14). In addition, both the symptoms and influencing factors of sleep problems in long-lived populations have varied patterns compared to the symptoms and factors among younger generations (15,16). Thus, it is imperative to verify tools for measuring sleep quality among this exceptionally aged population.…”
Section: Introductionmentioning
confidence: 99%
“…A certain degree of heritability for sleep–wake patterns and insomnia has been suggested [ 48 , 49 ], but the mechanisms involved are still under investigation, and its association with longevity is controversial. In fact, the empirical support for an increase in mortality risk with insomnia is inconsistent, although it might be higher with the use of hypnotic medication [ 50 ], and previous research did not show significant differences in sleep patterns between centenarians’ offspring and their controls [ 51 ]. In contrast, our familial longevity case group had significantly less insomnia than their matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disorders predispose persons to chronic diseases like obesity, depression, diabetes, and many cardiometabolic diseases, which are significantly associated with mortality and morbidity [ 121 , 122 ] [ 123 – 125 ]. Contrary, a steady pattern of waking and sleeping is associated with health promotion and longevity [ 126 ]. Prolonged disruptions of circadian rhythms are associated with negative health consequences [ 127 ].…”
Section: Circadian Rhythms Sleeping Habits and Nad + mentioning
confidence: 99%